2002
DOI: 10.1001/archneur.59.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Aquaporin 4 Expression in the Muscle Plasma Membrane of Patients With Duchenne Muscular Dystrophy

Abstract: The reduction in AQP4 in DMD muscles results from decreased levels of AQP4 mRNA in DMD myofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…These antisera were affinity purified. The affinity purified rabbit polyclonal AQP4 antibody against the C-terminal end of the rat AQP4 was also previously produced in our laboratory [18].…”
Section: Peptide Synthesis and Antibody Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antisera were affinity purified. The affinity purified rabbit polyclonal AQP4 antibody against the C-terminal end of the rat AQP4 was also previously produced in our laboratory [18].…”
Section: Peptide Synthesis and Antibody Productionmentioning
confidence: 99%
“…F0205, Denmark) diluted 1:50 in PBS for 60 min at room temperature. For the judgment of myofiber type [19], serial sections of HE or oil red O stained muscle samples and the immunostained muscle samples with anti-AQP7 or AQP9 antibody from obese DIO or control chow-fed mice were also immunostained with the affinity purified rabbit anti-AQP4 antibody at the IgG concentration of 5 µg/ml [18]. The immunostained muscles were examined using Nikon H 550L fluorescent microscope.…”
Section: Histopathological and Immunohistochemical Studiesmentioning
confidence: 99%
“…Vajda et al (2002) also showed the delayed onset of brain edema in dystrophin-null transgenic mice. In muscular dystrophy, reduced AQP4 expression was found in skeletal muscle plasma membrane (Crosbie et al 2002;Frigeri et al 2002;Wakayama et al 2002). Frigeri et al (2001) reported that the AQP4 mRNA content of mdx mouse muscles and brains was qualitatively the same as that of mdx control mouse muscles and brains, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the OAs were severely reduced and the anti-AQP4 antibody immunoreactivity was markedly reduced in these muscle plasma membranes. We reported that the severely decreased AQP4 expression of DMD muscles was due to the decreased AQP4 mRNA content of DMD muscles (Wakayama et al 2002). We thought whether the decreased AQP4 expression of mdx mice was due to the same mechanism as described in DMD muscles, and were interested in the measurement of the AQP4 mRNA content of mdx mouse muscles.…”
Section: Real-time Quantitative Reverse Transcription Polymerase Chaimentioning
confidence: 99%
See 1 more Smart Citation